eHealth technology and Internet resources: barriers for vulnerable populations. - Cashen MS; Dykes P; Gerber B (Journal of Cardiovascular Nursing)
Disparities in accessing health information exist for various vulnerable populations. Reviewing access issues for those seeking and/or needing health information suggests that there are many factors that may inhibit access. These include a wide diversity in the education, background, and needs of those seeking information, and the distribution of information among many disciplines and information sources. The most needy among this group may require extensive, multispecialty healthcare and may have particular problems with access, treatment adherence, and working within the healthcare system.